Failure investigation on reheater tube due to deposit and wall thinning - Purbolaksono J.; Tarlochan F.; Rahman M.M.; Nordin N.F.; Ahmad B. (2023)
Failure analysis of a reheater tube showed that the failure was caused by overheating and wall thinning. Finite element modeling, dimensional measurements, and microscopic examinations were performed to investigate the root cause of the failure. Wall thinning, due to excessive coal-ash corrosion, and overheating, due to scale buildup on the tube were measured, and estimations, the average corrosion and scale growth rates, were made. The combination of excessive scale formation on the inner tube surfaces and wall thinning due to coal-ash corrosion on the outer tube surfaces combined to cause the failure of the reheater tube. 2009 ASM International.